PENERAPAN METODE ECONOMIC ORDER QUANTITY (EOQ) DALAM ANALISIS PENGENDALIAN PERSEDIAAN SEMEN PADA PT. PANORAMA READY MIX. - Wahyuni, Sri (EKONOMIA, 2013)
Basically control is needed in a business organization, because control is a way to control or manage the activities in an organization or company to keep the stability of the company in a position that is already planned. Milton F. Usry (2004:5) gives the definition of â€œControl is a systematic effort to achieve company goals by comparing the performance with the plan and make the appropriate action to correcting important differencesâ€.The purpose of this study was to determine whether the application of inventory control using Economic Order Quantity (EOQ) can minimize inventory costs.Analysis tools used this study using a method that can calculate the minimum inventory as a measure of determining the amount of inventory is the analysis of Economic Order Quantity (EOQ).